2022
DOI: 10.1111/sltb.12871
|View full text |Cite
|
Sign up to set email alerts
|

When the United States says you do not belong: Suicide‐related thoughts and behaviors among immigrant young adults varying in immigration legal status

Abstract: Background:The number of immigrants in the United States and the risk of suicide among minoritized individuals have increased. Little research has examined the impact of immigration legal status on suicide-related thoughts and behaviors (SRTB), despite theoretical and empirical work suggesting that feelings of burdensomeness and failure to belong (prominent among immigrants) are risk factors. Methods:We examined a diverse sample of foreign-born young adults (18-25; N = 366). Data collection utilized the Suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As these sentiments have become commonplace, Latinx immigrant youth have increasingly found themselves in communities that are hostile to them and their families. This hostility exacerbates Latinx immigrant youth’s feelings of “otherness” and prevents them from developing a sense of connectedness to their community (Gonzales et al, 2013; Perez, 2021; Rojas Perez et al, 2023; Venta et al, 2022; Wray-Lake et al, 2018). This disconnection and foreignness are often exacerbated when Latinx immigrant youth encounter these cultural stressors in the school setting.…”
Section: Cultural Stressors Across Multiple Levels and Domains Of Inf...mentioning
confidence: 99%
“…As these sentiments have become commonplace, Latinx immigrant youth have increasingly found themselves in communities that are hostile to them and their families. This hostility exacerbates Latinx immigrant youth’s feelings of “otherness” and prevents them from developing a sense of connectedness to their community (Gonzales et al, 2013; Perez, 2021; Rojas Perez et al, 2023; Venta et al, 2022; Wray-Lake et al, 2018). This disconnection and foreignness are often exacerbated when Latinx immigrant youth encounter these cultural stressors in the school setting.…”
Section: Cultural Stressors Across Multiple Levels and Domains Of Inf...mentioning
confidence: 99%
“…(2018) found among Mexican undocumented adults that experiencing interpersonal discrimination due to being undocumented was the strongest predictor of clinically significant psychological distress, adding that they were 5.47 times more likely to have clinically significant psychological distress compared to those who had not experienced discrimination. As has already been established, undocumented individuals are at-risk for mental health problems and negative developmental outcomes (Cadenas & Nienhusser, 2021;Venta et al, 2022) and discrimination has been linked with worsening these risks Cobb et al, 2019). Despite discrimination being documented as a hindrance, the present study considers discrimination as a spark that ignites the potential for resistance through civic engagement among undocumented young adults.…”
Section: Anti-immigrant Discriminationmentioning
confidence: 79%
“…Regarding harmful societal perceptions, a study conducted with a sample of Brazilian immigrants found that many participants felt as though their feelings of being discriminated against were primarily due to their racial classification, trouble with speaking English, or being perceived as Hispanic and undocumented, as they were aware of Latinx and Hispanic undocumented individuals being primary targets of anti-immigrant discrimination in the U.S. (Joseph, 2011). This awareness of one's otherness-or being deemed as other-subjects undocumented individuals to feeling like they do not belong (Enriquez et al, 2019;Venta et al, 2022). Indeed, in feeling like one does not belong and consequently being subjected to unfair treatment, there can be consequences for poor psychological well-being and life satisfaction (Cobb et al, 2019).…”
Section: Anti-immigrant Discriminationmentioning
confidence: 99%